Feminism and the Politics of Creative Labour: Fashion Micro-enterprises in London, Berlin and Milan. Issue 100 (3rd April 2019) - McRobbie, Angela; Strutt, Dan; Bandinelli, Carolina
ABSTRACT: This article makes the case for fashion – as part of the creative industries and a major employer of women, as well as a significant space for self-organised work – to attract more sustained attention from feminist scholars in order to develop a stronger policy lobby for the sector with priority given to quality livelihoods. Drawing on interviews and observations carried out within the course of a three-year study which investigated working lives of fashion designers (predominantly female) in London, Berlin and Milan, the argument presented emerges from an analysis which focused on two key factors: the impact of adverse economic circumstances following the euro-crisis of 2008 and the role of urban cultural policies in the ability of designers to establish a creative practice. With the help of three provisional concepts, each of which relies on questions of space/place, we suggest that this expansive sector contains potential to become a more equitable and socially engaged field, particularly with reference to women's working lives and through the development of regionalised centres with an emphasis on doing fashion differently.